The architecture of the Nałęczów Nursery in the context of designing kindergarten and care facilities - Przesmycka, Natalia; Boguszewska, Kamila Lucyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
The article presents the history and architecture of the nursery building in Nałęczów, one of the first buildings of this type erected in rural areas of the Lublin region. This building escapes the clear stylistic classification and is an inseparable element of the cultural landscape of Nałęczów. In an attempt to determine the implementation of the Nałęczów project in comparison with other shelters created in a similar period of time, this paper takes a broader look at the problems of establishing the institution of nurseries and later transformations of such objects.